Produksi Fruktosa dari Tongkol Jagung Sebagai Gula Rendah Kalori - Mahyati, Mahyati; Pasanda, Octovianus SR (INTEK: Jurnal Penelitian, 2016)
Corn cobs as waste organic agricultural having content±45% cellulose. Cellulose is a biopolymer that can be converted into glucose. Glucose can be produced by A.niger and T.ressei through fermentation process. Glucose in generate can be developed to become fructose syrup through a process isomerisasi with enzymes glucoisomerase prodused by Streptomyces Sp. This research using corn cobs yellow as a source of cellulose for the production of fructose. The purpose of this research is to find concentration fructose syrup obtained from fermentation process. Convertion cellulose be done in enzimatis use A.niger and T.ressei through the fermentation process by adding Saccharomyces cerevisiae. The process continues with isomerization use Streptomyces Sp. The process isomerization done with variations time is 1,2,3, and 4 hour and variation pH 6,7, and 8. Analysis concentration glucose and fructose of fermentation product performed with GCMS. The highest result obtained was fermentation 1 hour at pH 6 with glukoce 6,7% and fructose 16,22%.